Amino Acid Polymorphisms in the VHIID Conserved Motif of Nodulation Signaling Pathways 2 Distinctly Modulate Symbiotic Signaling and Nodule Morphogenesis in Medicago truncatula - Kovacs, Szilárd; Fodor, Lili; Domonkos, Agota; Ayaydin, Ferhan; Laczi, Krisztián; Rákhely, Gábor; Kalo, Péter (Frontiers in Plant Science, 2021)
Legumes establish endosymbiotic association with nitrogen-fixing soil bacteria. Following the mutual recognition of the symbiotic partner, the induction of the signaling pathway and the subsequent activation of genes required for rhizobial interaction control this symbiotic process. One of the protein complexes regulating the nitrogen-fixing root nodule symbiosis is formed by GRAS domain regulatory proteins Nodulation Signaling Pathway 1 and 2 (NSP1 and NSP2) that control the expression of several early nodulation genes. Here, we report the comparative analysis of a novel and the formerly identified (nsp2-3) point mutant alleles impaired in the NSP2 gene. Both mutants carry a single amino-acid substitution in the VHIID domain of the NSP2 protein. We found that the two mutant alleles show dissimilar root hair response to bacterial infection and although the nsp2-3 mutant develops aberrant infection threads, rhizobia were able to colonize nodule cells in this mutant. The encoded NSP2 proteins of the nsp2-3 and the novel nsp2 mutants interact with NSP1 diversely and in consequence, the activation of early nodulin genes and nodule organogenesis are arrested in the strong new nsp2 allele. The novel mutant with amino acid substitution in NSP2 shows similar defects in symbiotic responses to the formerly identified nsp2-2 mutant carrying deletion in the NSP2 gene. Additionally, we found that rhizobial strains induce nodule formation in a temporal shift on the roots of the ns2-3 weak allele. Our work highlights the importance of a conserved residue in the VHIID motif of NSP2 that is required for the formation of NSP1-NSP2 signaling module and our results imply the involvement of NSP2 during the differentiation of symbiotic nodule cells.